IMPLEMENTASI PROGRAM PENANGGULANGAN GIZI BURUK PADA ANAK BAWAH LIMA TAHUN PADA DINAS KESEHATAN KABUPATEN DONGGALA PROVINSI SULAWESI TENGAH - Lisang, Amran Gatah (Katalogis, 2017)
The goal of this research is to analyze and provide an overview Prevention Program Implementation Malnutrition in Children Under Five Years On Donggala District Health Office of Central Sulawesi Province. This study refers to the opinion of Edward III of Implementation which includes elements of Interest, Communication, Resources, Disposition, and Bureaucratic Structure. This type of research in achieving the purposes and objectives of the research are descriptive method qualitative approach. The research location in Donggala Health Office. Informants in this study were selected purposively as many as five people. Data collection techniques used were observation, interview, and documentation. The data analysis was performed with data reduction procedures, presentation of data and draw conclusions. The results of this study explained that the implementation Program countermeasures Malnutrition Children Under Five Years On Health Office Donggala, judging by the theory of policy implementation raised by Edward III, which includes Communications, Resources, Disposis and Strukutur Bureaucracy has not overall have not been going well. This is because of all these factors there is still a factor Source Day that has not gone well, while the communication factor, disposition, and structural Bureaucracy has been well implemented.